Inhibition of fucosylation by 2-fluorofucose attenuated acetaminophen-induced liver injury via its anti-inflammation and anti-oxidative stress effects - Liu, Zhaoguo; Tu, Mengjue; Shi, Jianan; Zhou, Hong; Meng, Guoliang; Gu, Jianguo; Wang, Yuqin (Frontiers in Pharmacology, 2022)
Fucosylation is a common glycan terminal modification, which has been reported to be inhibited by 2-fluorofucose (2FF) both in vivo and in vitro. The present study aimed to investigate the effect of 2FF on acetaminophen (APAP)-induced acute liver injury, and further clarified the possible mechanisms. In the present study, inhibition of fucosylation by 2FF relieved APAP-induced acute liver injury in vivo. Pretreatment with 2FF remarkably suppressed APAP-induced oxidative stress and mitochondria damage. 2FF markedly enhanced the nuclear translocation of nuclear factor erythroid 2-related factor 2 (Nrf2) and simultaneously promoted the expression of downstream proteins including HO-1 and NQO1. Furthermore, pretreatment with 2FF significantly suppressed the expression of inflammation-associated proteins, such as COX2 and iNOS. The data from lectin blot assay revealed that the alteration of α1,6-fucosylation was involved in APAP-induced acute liver injury. The second part of this study further confirmed that the enhancements to antioxidant capacity of 2FF pretreatment and α1,6-fucose deficiency were related to Nrf2/keap1 and NF-κB signaling pathways in HepG2 cells. Taken together, the current study suggested that 2FF might have a potential therapeutic effect for APAP-induced acute liver injury.